Children's Interpersonal Intelligence in Broken Home Families: Trans-perspective Analysis and Multi-aspect Sublimation - Fatmaningsih, Etika; Fakhruddin, Asef Umar (UM Purwokerto Press, 2025)
Interpersonal intelligence is fundamental for children. However, in a broken home, children are very likely to be distorted from the potential to get direction and assistance so that the development of their interpersonal intelligence is optimal. As a result, children's interpersonal intelligence in broken home families can become an anomaly, because children have the potential to become victims. Elementally, this research method uses interviews and in-depth observations, so that every aspect can be read comprehensively. Furthermore, it is also supported by trans-perspective analysis in order to analyze how the sublimation of interpersonal intelligence in broken home families, which is also the purpose of the research. The projection of the findings of this study is that if you surrender to the situation and are passive to reality, a broken family can affect children's interpersonal intelligence. The implication is that children become asocial individuals, moody, not enthusiastic about learning and avoid social interaction.